2004
DOI: 10.1111/j.1532-950x.2004.04052.x
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐Emptive Epidural Ketamine or S(+)‐Ketamine in Post‐incisional Pain in Dogs: A Comparative Study

Abstract: Although anesthetic and analgesic potency of S(+) ketamine is twice that of ketamine, the racemic form is seemingly better for post-incisional hyperalgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 34 publications
0
14
0
1
Order By: Relevance
“…This isobolographic study demonstrated that ifenprodil potentiates the antihyperalgesic effect of ketamine, in rats. Based on that, in this present study we clinically demonstrated that ifenprodil (0.03 mg kg-1) was effective to significantly enhance the antihyperalgesic effect induced by the usual dose of ketamine (Duque et al, 2004).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…This isobolographic study demonstrated that ifenprodil potentiates the antihyperalgesic effect of ketamine, in rats. Based on that, in this present study we clinically demonstrated that ifenprodil (0.03 mg kg-1) was effective to significantly enhance the antihyperalgesic effect induced by the usual dose of ketamine (Duque et al, 2004).…”
Section: Discussionmentioning
confidence: 88%
“…Finally, inflammatory processes in peripheral tissues may facilitate the activation of NMDA receptors in the spinal cord (Stanfa et al, 1996). Interestingly, the findings of this study demonstrated that modulation of NMDA receptors by ifenprodil can improve the antihyperalgesic action of a known effective dose of ketamine (Duque et al, 2004). The analgesic effects of ketamine appear to occur by the blockade of NMDA receptors when the coupled ion channel is closed (Orser et al, 1997).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Similar results were described by Sano et al (2010), who reported a significant decrease in CTT values after the use of morphine (0.2 mg/kg) for peribulbar block in dogs. Perhaps, the reduction of CTT in KET may be resulted by the antinociceptive and analgesics effects of ketamine as reported in different species (SEGURA et al, 1998;DUQUE et al, 2004) after epidural administration. Other authors observed similar results related to the peripheral and antinociceptive action of ketamine and morphine used alone or in combination (LILLESØ et al, 2000;KAPITZKE et al, 2005).…”
Section: Discussionmentioning
confidence: 99%